Value Chain Analysis for Strategic Management Accounting: Case Studies of Three Private Universities in Kupang - East Nusa Tenggara - Merici Minggu, Angela; Chariri, Anis; Jatmiko Wahyu P, Tri (KnE Social Sciences, 2020)
This study aims to describe the concept of value chains as the basis for strategic management accounting design in three private universities in Kupang (East Nusa Tenggara). A qualitative approach with multiple case study methods is used in this study by focusing on the problems that arise as a result of the enactment of Law No. 12 of 2012 concerning PTN-BH concerns autonomy and decentralization. Semi-structured interviews were conducted at three leaders of private universities, they were chosen because they were considered to have the greatest role in improving the quality of the institutions they lead. This research offers a contribution in identifying competitive advantages in an effort to improve the quality of private universities. In addition, contributions in designing strategic management accounting are also carried out in order to assess their relative position against competitors. This study found ten main themes, namely the number of new students, the ratio of lecturers to students; recruitment of new lecturers; use of technology; national and international publications; public services; quality of lectures; quality of graduates and waiting period; infrastructure development and promotion. Value chain analysis is proven to be able to breaking down the university to determine relevant strategies in order to improve sustainable quality. This research also shows that the case study method can be a powerful tool in analyzing the value chain concept. Keywords: Value Chain, Strategic Management Accounting, Private Universities